Structural studies and impedance spectroscopy of sol–gel derived Bi0.9Pr0.1FeO3 nanoceramics. (May 2016) - Mahato, Dev K.; Saha, Sujoy; Sinha, T.P.
Abstract: Nano-crystalline Bi0.9 Pr0.1 FeO3 (BPFO) ceramics have been synthesized by a sol–gel technique. The Rietveld refinement of the room temperature powder X-ray diffraction pattern confirms that the BPFO crystallizes in the rhombohedral R3c space group symmetry. SEM image of the sintered BPFO ceramic shows particles with same shape and fine grain morphology with the average grain size of 53±12 nm. The electrical properties of the ceramic are analysed by impedance spectroscopy. Grain and grain-boundary effect is observed in the material at lower temperature range which has been confirmed by electric modulus formalism. The ac conductivity spectrum obeys the Johnscher's power law. The activation energy calculated from dc conductivity is found to be 0.373 eV, which represents the conduction of small polaron over barrier between two sites of the lattice. Graphical abstract: Rietveld refinement shows that crystal structure of BPFO is rhombohedral with the space group R3c with the following distribution of ions in crystallographic positions: Bi 3+ /Pr 3+ /Fe 3+ ions at (2a) with 3 symmetry and O 2− ions at (6b) with 1 symmetry. Highlights: BPFO nanoparticles are obtained at a low temperature (873 K). The conductivity of the BPFO is one order higher than BFO (with particle size 50 nm). Crystal structure is rhombohedrally distorted due to Pr-doping. A two-site polaron hopping process between Fe 2+ and Fe 3+ is observed. Grain and grain-boundary effect is confirmed by electric modulus formalism.